Investigating the impact of internship experience on work readiness among hospitality program students: the moderating role of student mindfulness - Alharethi, Thaib; Awan, Maheen Iqbal; Saleem, Muhammad Shoaib (Frontiers in Education, 2025)
IntroductionThe hospitality industry and its success are linked to the presence of a talent pool that is well-prepared to serve diversified customers. Saudia’a Vision 2030 focuses much on the tourism industry as it anticipates a surge in international tourists. This study evaluated the impact of internship experience on the work readiness of students pursuing degrees in the hospitality industry. Further, the study assessed the direct role of mindfulness over students’ ability and role clarity and the moderating role of individual mindfulness between internship experience and work readiness (ability and role clarity).MethodsThe study employed a quantitative research method through a cross-sectional approach and evaluated the proposed model through structural equation modeling (covariance-based method). The path model was assessed using 5,000 bootstrapping samples of 361 responses from higher education graduates.ResultsStudy findings highlighted that internship experience significantly and positively impacted students’ ability and role clarity. The moderating role of individual mindfulness was significant, and it augmented the magnitude of the internship experience with students’ role clarity and ability.DiscussionStudy findings suggest that incorporating mindfulness in the lives of students and organizations can be of great value from the learning and performance perspective. Providing students with enriched internship experience and introducing the workforce toward individual mindfulness will benefit academia, industry, and students.